2013
DOI: 10.1002/gcc.22055
|View full text |Cite
|
Sign up to set email alerts
|

Identification of PPAP2B as a novel recurrent translocation partner gene of HMGA2 in lipomas

Abstract: Most lipomas are characterized by translocations involving the HMGA2 gene in 12q14.3. These rearrangements lead to the fusion of HMGA2 with an ectopic sequence from the translocation chromosome partner. Only five fusion partners of HMGA2 have been identified in lipomas so far. The identification of novel fusion partners of HMGA2 is important not only for diagnosis in soft tissue tumors but also because these genes might have an oncogenic role in other tumors. We observed that t(1;12)(p32;q14) was the second mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 48 publications
0
27
1
Order By: Relevance
“…It has been suggested that high mobility group (HMG) proteins act as architectural factors and coordinate cell proliferation and differentiation in adult adipose tissue [36,37,46]. Research revealed that the HMGA2 gene is frequently disrupted in human solid tumours of a differentiated mesenchymal origin such as lipoma [46].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that high mobility group (HMG) proteins act as architectural factors and coordinate cell proliferation and differentiation in adult adipose tissue [36,37,46]. Research revealed that the HMGA2 gene is frequently disrupted in human solid tumours of a differentiated mesenchymal origin such as lipoma [46].…”
Section: Discussionmentioning
confidence: 99%
“…Research revealed that the HMGA2 gene is frequently disrupted in human solid tumours of a differentiated mesenchymal origin such as lipoma [46]. Furthermore, it has been postulated that PPAP2B, a member of the lipid phosphate phosphatases family, plays a role in human adipogenesis [36]. Finally, pRB, a product of the human RB-1 gene, might play a key role in adipogenesis [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports on microdeletions within 12q14 region ranged from 1.83 Mb to 10.12 Mb with a 378Kb smallest region of overlap containing the HMGA2 and IRAK3 genes [3][4][5][6][7][8][9][10][11][12]. Several authors confirmed the association between growth impairment and loss of HMGA2 gene as a common feature in the 12q14 microdeletion syndrome [3][4][5].…”
Section: Introductionmentioning
confidence: 87%
“…3 have not yet been reported and the previously reports involving HMGA2 gene gains of function were acquired rearrangements related with potentially malignant conditions. The majority were HMGA2 fusions with partner genes and subsequently formation of chimeric transcripts with gain of HMGA2 gene function and tumor formation [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%